2008
DOI: 10.1021/jf8020893
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Kombucha Tea—Effect of Temperature on Tea Components and Free Radical Scavenging Properties

Abstract: Kombucha tea is sugared black tea fermented with a consortium of acetic acid bacteria and yeasts (tea fungus) for 14 days. The tea tastes slightly sweet and acidic. The formation of tea fungal biofilms during storage is a big problem when kombucha tea is being stored and commercialized. Various thermal treatments have been tried for long-term storage of kombucha tea. The present study revealed the influence of heat on the biochemical constituents and the free radical scavenging properties of kombucha tea. Heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 25 publications
1
43
0
2
Order By: Relevance
“…In a study on the preservation of kombucha tea-effect, Jayabalan et al found that heat treatment at 60, 65, and 68 °C for 1 min led to a decrease in tea polyphenols and free radical scavenging properties during storage. It was thus suggested that heat treatment was not a suitable method for kombucha preservation (Jayabalan et al, 2008a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on the preservation of kombucha tea-effect, Jayabalan et al found that heat treatment at 60, 65, and 68 °C for 1 min led to a decrease in tea polyphenols and free radical scavenging properties during storage. It was thus suggested that heat treatment was not a suitable method for kombucha preservation (Jayabalan et al, 2008a).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the concentration of acetic acid reached maximum on the 15 th day (green tea kombucha), while glucuronic acid concentration reached maximum on 12 th day (black tea kombucha) of fermentation, respectively. In a later study, these authors also analyzed the changes in free-radical scavenging ability of kombucha during fermentation (Jayabalan et al, 2008a). Moreover, there is a interesting report that lactic acid bacteria obtained from kefir can increase the productivity of bacteria in kombucha to higheffectively get d-saccharic acid 1, 4 lactone (Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Green tea (Camellia sinensis) is the second most consumed beverage in the world and has caused great interests among researchers [1][2][3][4]. The polysaccharides from tea have shown to have a variety of bioactivities, such as immunostimulating [5], hypoglycemic [6,7], and anti-bacterial activities [8].…”
mentioning
confidence: 99%
“…The tea was then poured in sterile glass bottles to which 3% freshly grown tea fungus that had been previously cultured in the same medium for 28 days was added. The bottles were covered with sterile muslin cloth and fastened tight.The fermentation was carried out at room temperature (RT) in static condition and in dark for 28 days (Jayabalan et al, 2008).…”
Section: Tea Preparationmentioning
confidence: 99%